Effect of co-precipitation and solid-state reaction synthesis methods on lithium-rich cathodes Li1.2Ni0.2Mn0.6O2 - Rodríguez Carrillo, Augusto Manuel (2022)
Lithium-rich oxides (Li1.2Ni0.2Mn0.6O2) were obtained by two synthesis routes: co-precipitation method and solid-state reaction. Both materials showed a high degree of crystallinity, and XRD analysis revealed intense and well-defined signals corresponding to the R3m and C2/m space groups of these types of compounds, with a difference in the cationic order in the hexagonal structure layers. The cycling performances showed an initial discharge capacity of 200 mAh g−1 from the co-precipitated material, against the 150 mAh g−1 obtained from the solid-state reaction route but, unlike the large drop in the discharge capacity of the co-precipitated material after 160 cycles, the material obtained by solid-state reaction provided a slightly constant discharge capacity of ⁓120 mAh g−1 throughout cycling. The high initial discharge capacity of the co-precipitated material may be associated with the activation of the Li2MnO3 phase cycled at 0.2 C between 2.0–4.8 V and 2.0–5.2 V, the better cationic order and wider space between the layers of the LiMO2 phase. Therefore, the electrochemical performance could be directly related to those structural characteristics obtained thorough the selected synthetic procedures.